2016
DOI: 10.3389/fenvs.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

Iron, Cobalt, and Gadolinium Transport in Methanogenic Granules Measured by 3D Magnetic Resonance Imaging

Abstract: Description of processes such as bioaccumulation, bioavailability and biosorption of heavy metals in biofilm matrixes requires the quantification of their transport. This study shows 3D MRI measurements of the penetration of free (Fe 2+ , Co 2+ and Gd 3+ ) and complexed ([FeEDTA] 2− and [GdDTPA] 2− ) metal ions in a single methanogenic granule. Interactions (sorption or precipitation) between free metals and the biofilm matrix result in extreme shortening of the spin-spin relaxation time (T 2 ) and a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Many nuclei of atoms carry a quantum mechanical spin and thus a magnetic moment (Bartacek et al, 2016). If a strong polarizing magnetic field is used on those nuclei they become magnetized.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 2 more Smart Citations
“…Many nuclei of atoms carry a quantum mechanical spin and thus a magnetic moment (Bartacek et al, 2016). If a strong polarizing magnetic field is used on those nuclei they become magnetized.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…However, MRI has mainly been used in biofilm research to form a 2D or 3D image of the biofilm to show structural biofilm features (Franklin et al, 2015;Neu et al, 2010). For biofilm imaging, magnetic field used can vary from 0.7 to 14.1 Tesla (Bartacek et al, 2016). Caizán-Juanarena et al, 2019 used a magnetic field of 14.1 T to get (28 μm) 3 resolution 3D images of EABfs (Fig.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research studies have mainly focused on biofilm structure, transport of water (i.e. diffusion and flow) and transport of metal ions in and around biofilms structures (Bartacek et al, 2016;Herrling et al, 2017;Manz et al, 2005;Phoenix & Holmes, 2008;Ramanan et al, 2010;Seymour et al, 2004;Wieland et al, 2001), and grown on carriers, even with complex geometry (Graf von der Schulenburg et al, 2008;Herrling et al, 2015Herrling et al, , 2017. Specifically, MRI research on biofilm growth on electrodes has revealed information about diffusion coefficients and metabolic activity (i.e.…”
Section: Chaptermentioning
confidence: 99%
“…to achieve higher spatial resolutions due to the smaller dimensions of biofilms, but biofilm studies have also been performed at very low field strengths of 0.7 T (e.g. (Bartacek et al, 2016)).…”
Section: Chaptermentioning
confidence: 99%